Conceptualising 'queercide': a quantitative exploration of the technical frames used in online reports on lesbian murders in South Africa. - van der Schyff, Marchant (Communicare, 2023)
South Africa remains one of the most dangerous places for women - lesbians in particular - to live freely and safely, where a culture of patriarchy and a lack of socio-economic opportunity are ubiquitous throughout its communities. While the Internet has given journalists a wider platform to provide insights about issues plaguing lesbians, there is very little information regarding the elements used in these online reports. This is not only due to the lack of language required to contextualise lesbian issues, but also persistent institutional and societal homophobia. This article describes the technical frames used in the online news reporting of four case studies of 'queercide'. Using a thematic coding sheet, data was collected from 70 online articles purposively selected based on a priori population characteristics. The study found technical elements, such as the length of online reports, credible sources used, and 'code-driven' and 'user-driven' elements identified in the coded online articles. The conclusion uncovers some clear trends enabling the construction of a Venn-type diagram, which presents insights into how the murder of lesbians (referred to as a sub-section of 'queercide' in the article) is being reported by online news media compared to contemporary theoretical discussions on how these cases should be reported on. This article situates 'queercide' within a conceptual framework for future studies, while the findings demonstrate how online articles on the killing of lesbians lack self-regulatory and sharing features that would improve their legitimacy in the minds of their readers.